CHALLENGES AND PERSPECTIVES IN TRAINING TEACHERS FOR ELEMENTARY SCHOOL NON-FORMAL EDUCATION IN CONTEMPORARY CHINA - Yanlin, Wu; Dovzhenko, Tatiana; Mkrtichian, Oksana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
China has seen significant changes in its educational landscape recently, with a growing focus on holistic education for primary school students. Alongside formal schooling, non-formal education has become increasingly important, seen as a vital supplement to traditional classroom learning. However, the Chinese government perceives the widespread enthusiasm among parents for non-formal education as a negative trend, hindering positive qualitative changes in formal education. There are concerns about the lack of control, particularly regarding ideological influence, educator training, and service quality within the non-formal education sector, which also involves substantial financial investment. This article, drawing from publicly available sources, assesses the current state of China's non-formal education sector and examines the measures undertaken by the government in the past five years to enhance the quality of educational services. Additionally, it explores the future prospects of non-formal education in China within the context of policies aimed at reducing student burdens and improving educational service quality. The focus of the study is on primary and elementary school students, as this age group constitutes the primary target audience for non-formal educational opportunities in modern China.